PENERAPAN AUDIT MANAJEMEN REKRUTMEN DAN SELEKSI SDM DI P.T. MAINDO INTERBUMI MENURUT PANDANGAN KRISTIANI - Susanto, Hana Debora Victoria; Hellena Putri Pramestika; Nany, Magdalena; Yahya Agung Kuntadi; Magdalena Elly Kurniawati (FKIP UKI TORAJA, 2024)
P.T. Maindo Interbumi's commitment to excellence is evident in everything it does, from its state-of-the-art production facilities to its knowledgeable and professional staff. The recruitment and selection process of human resources is a very important stage in an effort to obtain employees who have high productivity and commitment in achieving company goals. Therefore, it is necessary to conduct a management audit of the recruitment and selectionfunction of employees. The data collection techniques used are interviews and observations. Meanwhile, the analysis of management audit elements used identifies conditions, criteria, causes and consequences. To ensure that recruitment runs effectively, companies need to consider the diversity of recruitment channels, suitability for the position required, and cultural suitability and the company's long term needs. Overall, it is important for companies to compare selection costs with similar practices in other companies in order to manage recruitment budgets more efficiently, stay competitivein the labor market and ensure that the costs incurred are proportional to the results